1990
DOI: 10.1128/jvi.64.12.5840-5850.1990
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of sequence diversity in hypervariable regions of the external glycoprotein of human immunodeficiency virus type 1

Abstract: Nucleotide sequences in three hypervariable regions of the human immunodeficiency virus type 1 (HIV-1) env gene were obtained by sequencing provirus present in peripheral blood mononuclear cells of HIV-infected individuals. Single molecules of target sequences were isolated by limiting dilution and amplified in two stages by the polymerase chain reaction, using nested primers. The product was directly sequenced to avoid errors introduced by Taq polymerase during the amplification process. There was extensive v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
2
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(105 citation statements)
references
References 38 publications
(54 reference statements)
4
97
2
2
Order By: Relevance
“…2A), so as to generate pseudotyped viruses. Epitope insertions were made in all five variable-loop regions on gp120, which are generally thought to be relatively surface exposed on the trimer structure, given the often-observed accumulation of mutations in these regions and elicitation of NAbs to them during infection (19,49,63,68,69). Insertions were also made in the C1 and C2 constant segments.…”
Section: Resultsmentioning
confidence: 99%
“…2A), so as to generate pseudotyped viruses. Epitope insertions were made in all five variable-loop regions on gp120, which are generally thought to be relatively surface exposed on the trimer structure, given the often-observed accumulation of mutations in these regions and elicitation of NAbs to them during infection (19,49,63,68,69). Insertions were also made in the C1 and C2 constant segments.…”
Section: Resultsmentioning
confidence: 99%
“…[36][37][38][39][40][41] This low CD4 density is similar to that present on macrophages. 21 The use of single genome amplification (SGA, or template endpoint dilution PCR) to amplify and clone full-length HIV-1 env genes from patient samples without PCR recombination [43][44][45][46][47] was essential in generating biologically relavant env clones for analyses of entry phenotypes. In contrast, many early studies of HIV-1 tropism used viral isolates that were generated by culturing patient samples with PBMCs and/or cell lines.…”
Section: Course Correction: Hiv-1 Can Be R5 T Cell-tropic X4 T Cell-mentioning
confidence: 99%
“…Significant genetic variation occurs within the human immunodeficiency virus (HIV) genome [reviewed by Leigh Brown, 19911. Many studies have shown that variation occurs in both a n inter-and intrapatient [Delassus et al, 1991[Delassus et al, , 1992Goodenow et al, 1989;Simmonds et al, 1990;Wain-Hobson, 19921 and that heterogeneity is not evenly distributed throughout the genome [Pedroza Martins et al, 1991, 19921. Thus, the hypervariable regions (Vl-V5) of the enu gene are significantly more heterogeneous than regions of the g a g gene [Leigh Brown and Monaghan, 1988;Balfe et al, 19901. The enu gene contains the principal neutralising determinant of HIV-1 [Rusche et al, 1988;Palker et al, 19881.…”
Section: Introductionmentioning
confidence: 99%